Career space in views of residents of the Rostov regio - O. Y. Posukhova (MGIMO University Press, 2013)
The article deals with career space in views of residents of Rostov region. The author analyzes the views of career opportunities, the place of work, the channels for employment and career advancement, the preferred occupations, limits of career and legitimization of career movements. It is stated that the movement in the career space is determined not so much by the professional resources, as by "family capital", and the lack of informal capital triggers rapid attainment of a career limit